(untitled) (Rigvedic Himalaya, 2024)
The solemn sadhu carrying his holy fire in a ceramic pot on his head are the last bearers of a specific part of millennia long traditions and Indo-European heritages. While the Vedic fires still shine and burn in many rituals throughout the sub-Indian continent, the particular fires ever burning and carried in ceramic pots represent perhaps one of the oldest and most original types of Vedic and Indo-European fires and fire rituals. The reasons why these types of fires were seen as the utmost holy and preserved as the most venerated and honourable gift from the gods cannot be sought under the scorching sun along the holy rivers in India, but among pastoral groups living in harsh and cold conditions and climates. Among early Indo-European pastoralists, the ever-burning fire represented the ultimate source and force of life, and these beliefs have been so strong and pervasive that the tradition and religious importance still shines and will continue to do so, because in their seemingly simplicity, these fire rituals reveal a profound complexity and they enable particular ritual possibilities and unique conceptualisations of divinities and their qualities